Response of Surabaya State University Students to Sports Biomechanics Textbook - Hakim, Abdul Aziz; Firmansyah, Awang; Widodo, Achmad; Jannah, Syaifathul (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
Sports Biomechanics is a subject that is considered not easy to understand, and exciting learning media are needed to facilitate the learning process, one of which is textbooks. This study aims to determine student responses to the textbook of Sports Biomechanics. The research method applied in this research is descriptive research with a quantitative analysis approach with a survey research design to respondents. The sample in this study was 30 students of the Sports Science class in 2018 and 2019. The provision that respondents were students of Sports Science class 2018 and 2019 who live in the Surabaya, Sidoarjo, and Gresik areas who have graduated and are taking the Sports Biomechanics course. The questionnaire in this study used the Linkert scale and adapted the questionnaire instrument (Hartati & Safitri, 2017). Analysis of the data using the Linkert formula and interpreting the data that has been obtained. The results of this study indicate that the average student response is obtained by 87,55% of students who feel that sports biomechanics textbooks are worthy as learning companions.